PREVALENCE OF KINESIOPHOBIA IN PREGNANCY RELATED LOW BACK PAIN (Journal of Medical & Health Sciences Review, 2025)
Background: Gestational low back pain (LBP) is common and can significantly affect a mother's health and behavior, making exercise and physical activity challenging. This difficulty may lead to kinesiophobia, a fear of movement, which is considered a risk factor for developing chronic LBP. Hence, our study was performed to find the occurrence of Kinesiophobia in pregnant females with low back discomfort in this territory.Aim: Our study aimed to inspect the occurrence of kinesiophobia in pregnancy related to lower back discomfort.Methodology: The descriptive cross-sectional study was conducted on n=212 gestating women diagnosed with LBP aged 18-40 years in all the three trimester of pregnancy presenting to gynecology outpatient department of the hospital of Rawalpindi and Islamabad between May 2024 and August 2024. Data was collected using non-probability convenient sampling technique with semi structured questionnaire, Numeric Pain Rating Scale for assessing pain intensity, and the Tampa Scale to measure degree of kinesiophobia. Results were described using means, standard deviations, frequencies, and percentages. Data analysis was performed using SPSS 27 version.Results: Majority of the females in this study were from third trimester with the mean + SD score of age is 27.0236 ± 4.48741 and prevalence of Kinesiophobia was positive in 132 out of 201 subjects, which is 62.3% prevalence.Conclusion: A noticeably high prevalence of kinesiophobia has been observed in pregnant women with LBP.